Differences of Ampicillin and Cefazolin Effects in Reducing hs-CRP Level in Premature Rupture of Membranes - Ahmad Bukhoeri; Syarief Thaufik Hidayat; Ediwibowo Ambari; Julian Dewantiningrum; Putri Sekar Wiyati; Besari Adi Pramono (Faculty of Medicine, Diponegoro University, 2021)
Background: Premature rupture of membranes (PROM) is a rupture of amniotic sac before delivery. PROM is associated with an increased incidence of preterm labor and infection. The use of prophylactic antibiotic may reduce the risks of infection. High-sensitivity C-reactive protein (hs-CRP) is an acute-phase reactant protein that is associated with PROM. How much effect of prophylactic antibiotic to hs-CRP level remains unclear.Objective: To compare the reduction in hs-CRP levels in premature rupture of membranes before and after given ampicillin or cefazolin.Methods: The design of this study was true experimental design (pre and post-test) conducted at Dr. Kariadi General Hospital Medical Center Semarang and Kartini General Hospital Jepara from September 2019 to January 2020. Study samples are pregnant women with premature rupture of membranes that came to the Emergency Department and Maternity Ward Dr. Kariadi General Hospital Medical Center Semarang and Kartini General Hospital Jepara. Samples were divided into two groups, a group treated with ampicillin and the other with cefazolin therapy. All samples were subjected to a hs-CRP examination. Statistical analysis was performed by Mann-Whitney and Wilcoxon.Results: There are no significant differences in the age variable (28.8 ± 6.54 vs 29.1 ± 5.93), gestational age (36.3 ± 2.55 vs 36.3 ± 2.90), and parity (2,2 ± 0.99 vs 2.47 ± 1.19) in the ampicillin and cefazolin groups (p> 0.05). In this study, 37.1% patients have a history of PROM while 62.9%. had no history of PROM. Reduction in hs-CRP levels after administration of ampicillin and cefazolin was significant (4.4 ± 2.65 mg/L vs 6.3 ± 4.43 mg/L, respectively, p = 0.03). The difference in the decrease in hs-CRP levels before and after given ampicillin and cefazolin was significant (p = 0.0001). Conclusion: There is a decrease in hs-CRP levels after the administration of ampicillin or cefazolin in PROM, whereas cefazolin induced higher reduction in hs-CRP levels. Ampicillin can still be used as a first-line prophylactic antibiotic in primary healthcare facilities.